Demokratisasi Dan Desentralisasi Partai Demokrasi Indonesia Perjuangan Dalam Pemilukada Provinsi Sumatera Utara Tahun 2018 - Junedi Lumban Gaol; Muryanto Muryanto; Heri Kusmanto (PERSPEKTIF, 2022)
The purpose of this study is to analyze and explain the existence of internal party democracy and the decentralization of party authority in the PDI-P through the Djarot-Sihar election and the basis for consideration of PDI-P carrying out the cadres of the central board of directors as a candidate pair for regional heads at the 2018 North Sumatra Provincial Election. qualitative research with descriptive analysis. This study is intended to describe and explain in depth the level of democracy and decentralization of power and authority of political parties in decision-making, especially in the nomination, determination up to the stage of submitting the Candidates for Governor and Deputy Governor in the General Election of Regional Heads of North Sumatra for the 2018-2023 Period. PDI-P implements a form of internal party democracy with a guided pattern where the General Chair has special authority in determining the form and procedure for administering internal democracy itself which is guaranteed by the Party Charter, Party Articles of Association, and Party Bylaws; The recruitment of candidates for regional heads and/or deputy regional heads is not carried out democratically in accordance with the principles of liberal democracy, where the decision making in the nomination of candidates rests with the General Chairperson of the Party. The determination of Djarot-Sihar as a candidate pair for governor and deputy governor of North Sumatra Province in the 2018 Regional Head General Election was based on party strategic considerations in accordance with the political calculations of the General Chair and party elite ranks.